IMPLEMENTASI PELATIHAN TEKNIS DALAM MENINGKATKAN KOMPETENSI PEDAGOGIK BAGI PENDIDIK MADRASAH TSANAWIYAH DI BALAI DIKLAT KEAGAMAAN BANDUNG : Studi Deskriptif pada Peserta Pelatihan Metodologi Pembelajaran Angkatan IV Tahun 2022 - Anggi Febri Hidayani, - (2022)
Religious Education and Training Center organizes Administrative, Educational, and Technical Training for Religious Personnel. This Learning Methodology Training is held to improve Madrasah Tsanawiyah educators' pedagogic competence. Pedagogic competence is the ability of educators to manage students' understanding of educational insights or foundations, student understanding, curriculum/syllabus development, learning design, implementation of educative and dialogical learning, evaluation of learning outcomes, development of students to actualize their various potentials. This study aims to determine the implementation of the training, which includes the stages, results, and follow-up of the learning methodology training at BDK Bandung. This study uses a descriptive method and a qualitative approach. Data collection techniques used are interviews, observation, and documentation studies. The research subjects were five people consisting of one organizer, one widyaswara, and two training participants. Based on the study's results, it can be seen that: 1) The stages of training consist of an analysis of training needs, formulation of training objectives, curriculum design, planning of training programs, implementation of training programs, evaluation of training programs. 2) The training results show an increase in the pedagogic competence of the trainees through the process evaluation and evaluation of results and supported by monitoring results from micro-teaching and RTL. 3) The follow-up implementation of this learning methodology training consists of two activities: a follow-up plan and monitoring of post-training activities. Keywords: Training, Pedagogic Competence, Educator